Prorifling of Elusive Organic Alalgam from Post-mortem Microbes: A Review Study - Amit Chauhan (Cutting Edge Research in Biology Vol. 3, 2023)
Atomization of comfy cadaver decomposition often results in evolution of a diversity of chemical compounds which are contemplated responsible for formed odor by decomposed body; termed as Volatile organic compounds. VOCs are usually blended with decomposition and cater potential to study the profile of chemical compounds which are produced from different microbes. Researchers have taken many initiatives to study about VOCs from mainly 3 post-mortem microbes of pig carcass. The species were inoculated using standard nutrient agar in head space vials. This study was initiated to get VOC profiling form post-mortem microbes and to impel time since death. By this time, no study has been initiated on human being, therefore, we tried to study the VOC produced by rat and pig carcass from post-mortem microbes by using GC-MS using SPME arrow method. It was observed that each microbial species produces different profile and production of VOC’s increase along with the time interval and can be used for determination of death from human remnant’s microbes.